Socialization and Training on Making Instruments for Arguing Skills Students in Madrasah Aliyah School - Yusnidar, Yusnidar; Harizon, Harizon; Haryanto, Haryanto; Astalini, Astalini; Darmaji, Darmaji; Suryati, Sri; Salsabilla Nurma Yahya, Gita (Integrated Science Education Journal, 2024)
Research objectives: The objectives of this study are to introduce and improve teachers' ability in designing student argumentation assessment instruments in measuring students' level of understanding in learning. Ultimately, it will help students develop good and correct argumentation skills during the learning process. Methodology: The method used in this study is a quantitative method. In using this method, the researcher uses a research design in the form of a questionnaire. By combining this method and design, the research results will be obtained in the form of numbers. The subjects in this study were teachers at Mtss Al-Hidayah. Kebon IX. The results of this study will later become a reference for how this research is conducted and what conclusions can be obtained from the implementation of this research. Main Findings: In the research related to the implementation and application of argumentation instruments, it was found that more than 50% of teachers agreed to implement this argumentation ability instrument. It is seen that teachers strongly agree with the existence of argumentation ability instruments. Teachers are interested and also want to try the argumentation skills instrument. Novelty/Originality of this study: This study is rarely conducted and this study is also quite interesting. From the discussion session, there are still many teachers who do not know about the existence of this argumentation ability instrument. Teachers are interested in implementing this argumentation ability instrument not only in science learning, but also in other subjects.